2017
DOI: 10.1007/s10658-017-1358-7
|View full text |Cite
|
Sign up to set email alerts
|

Fast detection by loop-mediated isothermal amplification (LAMP) of the three begomovirus species infecting tomato in Panama

Abstract: Potato yellow mosaic Panama virus (PYMPV), Tomato leaf curl Sinaloa virus (ToLCSiV) and Tomato yellow mottle virus (TYMoV) of genus Begomovirus (family Geminiviridae) are the only three begomovirus species detected infecting tomato (Solanum lycopersicum L.) in Panama. PYMPV, ToLCSiV and TYMoV induce symptoms of stunting, yellowing, curling, distortion of leaves and reduction of fruit size and cause important economic loses. A loop-mediated amplification under isothermal conditions (LAMP) assay was developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To diagnose several important DNA and RNA plant viruses, LAMP and reverse transcription LAMP (RT-LAMP) have been used. These viruses include Squash leaf curl virus (SLCV) [35], Tomato chlorosis virus (ToCV) [36], Cucurbit chlorotic yellows virus (CCYV) [37,38], Tomato yellow leaf curl virus (TYLCV) [39], Tomato spotted wilt virus (TSWV) [40], Cucumber mosaic virus (CMV) [41], Potato virus Y (PYV) [42], Potato leafroll virus (PRLV) [43], Cucumber green mottle mosaic virus (CGMMV) [44], Chinese wheat mosaic virus (WCHMV0) [45], Barley yellow dwarf viruses (BYDV) [46], Japanese yam mosaic virus (JYMV) [47], Plum pox virus (PPV) [48], Tobacco mosaic virus (TMV) [49], nine rice-infecting viruses [50], and three begomoviruses infecting tomato in Panama, i.e., Potato yellow mosaic Panama virus (PYMPV), Tomato leaf curl Sinaloa virus (STLCV) and Tomato yellow mottle virus (TYMV) [51]. However, no LAMP technique for the identification of CuLCrV has been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…To diagnose several important DNA and RNA plant viruses, LAMP and reverse transcription LAMP (RT-LAMP) have been used. These viruses include Squash leaf curl virus (SLCV) [35], Tomato chlorosis virus (ToCV) [36], Cucurbit chlorotic yellows virus (CCYV) [37,38], Tomato yellow leaf curl virus (TYLCV) [39], Tomato spotted wilt virus (TSWV) [40], Cucumber mosaic virus (CMV) [41], Potato virus Y (PYV) [42], Potato leafroll virus (PRLV) [43], Cucumber green mottle mosaic virus (CGMMV) [44], Chinese wheat mosaic virus (WCHMV0) [45], Barley yellow dwarf viruses (BYDV) [46], Japanese yam mosaic virus (JYMV) [47], Plum pox virus (PPV) [48], Tobacco mosaic virus (TMV) [49], nine rice-infecting viruses [50], and three begomoviruses infecting tomato in Panama, i.e., Potato yellow mosaic Panama virus (PYMPV), Tomato leaf curl Sinaloa virus (STLCV) and Tomato yellow mottle virus (TYMV) [51]. However, no LAMP technique for the identification of CuLCrV has been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to highlight that samples infected with TYLCV, PepGMV and ToLCSiV were found in the border region with Panama. In this country, the bipartite begomoviruses Potato yellow mosaic Panama virus (PYMPV), ToLCSiV and ToYMoV have been reported (Herrera‐Vásquez et al, 2018). Furthermore, considering that B. tabaci MEAM1, which has been associated with the transmission of TYLCV, has also been reported in Panama (Brown & Bird, 1992; Kriticos et al, 2020), special attention should be paid to this border area to avoid or eventually control the transmission of TYLCV.…”
Section: Discussionmentioning
confidence: 99%
“…Keizerweerd et al showed that LAMP and real-time PCR had the same sensitivity in 0.1 ng for the detection of Puccinia kuehnii and reported that LAMP was specific and rapid [42]. Herrera-Vasquez and colleagues used LAMP for the detection of Begomovirus species infecting tomato; they report the same sensitivity between LAMP and PCR, but mention that LAMP is a rapid specific and cheap method [43]. LAMP isothermal amplification has already been used to detect Pseudomonas syringae pv.…”
Section: Discussionmentioning
confidence: 99%